2021
DOI: 10.2174/1874149502115010279
|View full text |Cite
|
Sign up to set email alerts
|

Durability Phenomena of Bitumen and Bituminous Pavement Materials

Abstract: The durability of asphaltic mixtures, in addition to traffic loading, is greatly influenced by the extremes environmental parameters. For instance, at higher temperatures, bitumen becomes soft, thereby reducing the stiffness of asphalt mixtures and making them vulnerable to rutting. On the other hand, at lower temperatures, the stiffness of bitumen is increased, reducing the flexibility of asphaltic concrete and rendering it prone to fatigue failure. Therefore, this evaluation is an extensive research study on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Binders are said to be durable if they resist deterioration or changes in physical characteristics over time [ 2 ]. Vehicle loading, endless exposure to climatic and environmental variables, and other factors make the ageing of bitumen mixtures inevitable.…”
Section: Factors Affecting Bitumen Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Binders are said to be durable if they resist deterioration or changes in physical characteristics over time [ 2 ]. Vehicle loading, endless exposure to climatic and environmental variables, and other factors make the ageing of bitumen mixtures inevitable.…”
Section: Factors Affecting Bitumen Propertiesmentioning
confidence: 99%
“…Road researchers throughout the world have focused their efforts, and industry has invested large resources and time in studying various elements and their interactions as they influence bitumen ageing [ 41 ]. Due to bitumen exposure to harsh environmental elements such as precipitation, temperature, air, and ultraviolet (UV) radiation, studies have shown that bitumen ageing has a significant impact on pavement durability [ 2 , 5 ]. For example, at a higher temperature, bitumen softens and loses rigidity, making it more susceptible to rutting.…”
Section: Factors Affecting Bitumen Propertiesmentioning
confidence: 99%
See 3 more Smart Citations